Reducing Stunting Rates Through Intervention for Adolescent Girls and Pregnant Women's Nutrition - Ridwan Fadjri Nur; Mila Yusnita; Sumiyati Sumiyati; Azis Hakim (Dinasti International Journal of Education Management And Social Science, 2023)
The condition of stunted physical and mental growth of children is a serious problem in human development in various countries, including Indonesia. Young women, as future mothers, have an important role in preventing stunting in the next generation. This article reviews the important role of maternal nutrition in efforts to reduce stunting rates in adolescent girls. First, this article will outline the risk factors for stunting that are often found in adolescent girls, such as malnutrition during their growth years, limited access to nutrition education, and limited knowledge regarding the importance of balanced nutrition. Next, we will discuss how good maternal nutrition during pregnancy and breastfeeding has a significant impact on child growth. Adequate and balanced maternal nutrition will provide children with good basic capital for their growth and development. Increase awareness of adolescent girls about the importance of balanced nutrition, through nutrition education in schools, outreach in the community, and better access to reproductive health services. In this context, the role of families, educators and the government in supporting young women to have a good understanding of nutrition will be emphasized, specifically maternal nutrition plays a key role in efforts to reduce stunting rates in future generations. Young women are a group that needs special attention in this effort, because they will become future mothers who will shape the quality of their children's growth and development. Comprehensive efforts, ranging from nutrition education to systematic support in getting good nutrition during pregnancy and breastfeeding.